Book review: Faces of the rule of law in Europe - Kmieć, Michał (Chrześcijaństwo-Świat-Polityka, 2025)
This review discusses the book Faces of the Rule of Law in Europe, edited by Michał Gierycz and Piotr Mazurkiewicz (2024), published by Vandenhoeck & Ruprecht in Göttingen. The volume is divided into three parts. The first, The Concept of the Rule of Law, provides a solid foundation for understanding this notion across centuries, emphasising the influence of Greek philosophy and Christianity. The second part, European Traditions of Understanding the Rule of Law, addresses the book’s central theme – namely, the diversity of rule-of-law traditions across European countries. It features contributions exploring the understanding of the rule of law in France, Germany, and Poland, as well as a distinctive case study on the Anglo-Saxon tradition in Australia, viewed through the lens of legal restrictions imposed during the COVID-19 pandemic. The final section, The Rule of Law in the European Union, examines the application of the rule of law within EU legal frameworks and highlights how the principle has been used as a political instrument to discipline member states that oppose the policy directions of EU institutions.